Enabling Orientation-Free Mmwave-Based Vital Sign Sensing with Multi-Domain Signal Analysis - Gong, Hanqin; Zhang, Dongheng; Chen, Jinbo; Li, Yadong; Xu, Guixin; Yuan, Yuqin; Hu, Yang; Chen, Yan (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2024)
Contactless vital signs estimation using mmWave radar has gained significant attention. However, existing studies are built upon the radar being directed facing the thorax to capture fine-grained vital signs, ignoring the angle variation between the radar and thorax in practical deployment. In this paper, we propose a spatial-temporal optimization model to estimate the human body orientations between the radar and thorax through extracting the multi-domain features of reflected signal. By aligning the signal variation captured from different angles, we can realize orientation-free vital sign sensing. The system achieves an average angle estimation error of 13.1°, and a 14.8% discrepancy reduction in terms of the mean absolute error of the signal captured at different angles.